2012
DOI: 10.1021/cm301864c
|View full text |Cite
|
Sign up to set email alerts
|

Low Temperature Epitaxial Oxide Ultrathin Films and Nanostructures by Atomic Layer Deposition

Abstract: Highly epitaxial and pure (001) CeO2 ultrathin films have been prepared by atomic layer deposition (ALD) at 275 °C on Y-stabilized ZrO2 cubic fluorite single crystal substrate using cerium β-diketonate (Ce(thd)4) and ozone (O3) as precursors. Substrate temperature and precursor pulses have been optimized to set the ALD window obtaining a growth per cycle of ≈0.2 Å/cycle. This extremely low growth rate has been identified as a key parameter to ensure epitaxial growth at these low temperatures. Post-thermal trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
50
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 70 publications
6
50
0
Order By: Relevance
“…[30][31][32] Most as-deposited ALD films are amorphous or polycrystalline, although epitaxial oxides can also be obtained in the as-deposited stage (< 300ºC) using structurally compatible buffer layers and single crystal substrates. [33][34][35][36] Among the ferroelectric perovskites, BiFeO 3 (BFO) is a stable, lead-free material that simultaneously presents ferroelectric and magnetic order at room temperature. 9,[37][38][39] In the literature, resistive-switching and photovoltaic responses have also been reported.…”
mentioning
confidence: 99%
“…[30][31][32] Most as-deposited ALD films are amorphous or polycrystalline, although epitaxial oxides can also be obtained in the as-deposited stage (< 300ºC) using structurally compatible buffer layers and single crystal substrates. [33][34][35][36] Among the ferroelectric perovskites, BiFeO 3 (BFO) is a stable, lead-free material that simultaneously presents ferroelectric and magnetic order at room temperature. 9,[37][38][39] In the literature, resistive-switching and photovoltaic responses have also been reported.…”
mentioning
confidence: 99%
“…1(c), a high resolution Z-contrast image, shows a coherent and sharp interface between LSMO and STO and a sharp interface between the LSMO layer and the ceria. Poor epitaxy is observed above a couple of atomic layers, which might be attributed to a high interfacial energy between defective perovskite and fluorite structures [11,46] rather than a difference in the lattice misfit (ε = +1.21%), as epitaxial ALD-CeO 2 has been achieved on fluorite YSZ single crystal substrates with a much higher lattice misfit (ε = −4.8%) [17]. Based on our early work, it is expected that the epitaxial quality of ALD-CeO 2 on CSD-LSMO could be further improved by optimizing the ALD process for this particular substrate and also by performing high temperature post annealing treatments, at least similarly to those where high quality epitaxial CSD-CeO 2 nanostructures are achieved on perovskite substrates [11].…”
Section: Ceo 2 /Lsmo/stomentioning
confidence: 99%
“…The as-deposited films are usually amorphous or barely crystalline and, in many cases, it would be beneficial to obtain them epitaxial directly in the as-deposited state. In fact, it has recently reported the possibility to obtain epitaxial oxide ALD thin films at 275°C [17]. Also, other authors have shown that ultrathin homoepitaxial layers with modified nanostructure can generate enhanced functionalities [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 It is possible to achieve precise film compositions and thickness control using ALD. 6 ALD functions by exposing a substrate to repeated pulses of a precursor gas containing a rare earth metal (RE) followed by a separate pulse of an oxidizing gas. Both gases undergo self-limiting reactions with the OH tails on the substrate surface.…”
Section: Introductionmentioning
confidence: 99%